Understanding the Trade Adjustment Assistance (TAA) for Farmers Program - Edward A. Evans (EDIS)
This publication discusses the Trade Adjustment Assistance (TAA) for Farmers program, intended to help producers of primary agricultural commodities adjust to increased foreign import competition. This is EDIS document FE498, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published January 2005.